Policy simulation and analysis of the optimal growth path of carbon emissions in Hubei Province’s tourism industry under low-carbon scenario - Long, Yuping; Li, Feng (Frontiers in Environmental Science, 2025)
IntroductionThe tourism industry significantly contributes to China’s economic growth, yet its high energy consumption poses substantial carbon emission challenges. Addressing these issues is essential to align the sector with national low-carbon development goals and ensure environmental sustainability.MethodsThis study develops a system dynamics model to evaluate carbon emission reduction pathways for the tourism sector under a low-carbon policy framework. Based on macroeconomic and tourism industry data from Hubei Province spanning 2013 to 2023, the model incorporates four subsystems: economic, energy, policy, and environmental. Comparative scenario simulations were conducted, including a baseline and a joint policy scenario integrating carbon taxation, technological subsidies, and green standard enforcement. Sensitivity analysis was performed to assess the robustness of the emission control strategies.ResultsUnder the baseline scenario, carbon emissions from the tourism industry are projected to rise from 1 million tons in 2013 to 1.8229 million tons by 2033, reflecting a 3.36% average annual increase. However, the joint policy scenario limits emissions to 1.412 million tons in 2033—a 22.5% reduction compared to the baseline—while maintaining tourism revenue at 742 billion yuan, only 0.4% below the baseline. Sensitivity analysis reveals that policy intensity and technological progress are critical factors in moderating emissions. Under the joint policy scenario, the 95% confidence interval for emissions narrows to between 1.387 and 1.439 million tons, with a fluctuation of less than 50,000 tons.DiscussionThe findings demonstrate that integrated low-carbon policy mixes can effectively curb carbon emissions in the tourism sector without significantly compromising economic output. This study not only provides empirical support for policy optimization but also uncovers the underlying drivers of tourism-related emissions, offering theoretical and practical guidance for advancing sustainable tourism and green economic transformation.